2020
DOI: 10.1017/s1368980019004221
|View full text |Cite
|
Sign up to set email alerts
|

Whole grain intake compared with cereal fibre intake in association to CVD risk factors: a cross-sectional analysis of the National Diet and Nutrition Survey (UK)

Abstract: Objective:To investigate how intakes of whole grains and cereal fibre were associated to risk factors for CVD in UK adults.Design:Cross-sectional analyses examined associations between whole grain and cereal fibre intakes and adiposity measurements, serum lipid concentrations, C-reactive protein, systolic blood pressure, fasting glucose, HbA1c, homocysteine and a combined CVD relative risk score.Setting:The National Diet and Nutrition Survey (NDNS) Rolling Programme 2008–2014.Participants:A nationally represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
2
14
2
Order By: Relevance
“…Cereal fibre intake was inversely related to total cholesterol, LDL-cholesterol and apo-B, while whole grain intake was not significantly associated to any of these CVD risk factors. This is in contrast to previous studies, whereby either no associations were found for either intake (28) , or inverse associations between the two were of similar magnitude (6) . Soluble fibre found in grains such as oats and barley may play a role in lowering cholesterol levels by reducing the absorption of cholesterol into the bloodstream, and this is supported by intervention trials (29) .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Cereal fibre intake was inversely related to total cholesterol, LDL-cholesterol and apo-B, while whole grain intake was not significantly associated to any of these CVD risk factors. This is in contrast to previous studies, whereby either no associations were found for either intake (28) , or inverse associations between the two were of similar magnitude (6) . Soluble fibre found in grains such as oats and barley may play a role in lowering cholesterol levels by reducing the absorption of cholesterol into the bloodstream, and this is supported by intervention trials (29) .…”
Section: Discussioncontrasting
confidence: 99%
“…It was interesting that in our study, after adjusting for cereal fibre intake, the inverse associations became stronger. Notably, these unexpected results support the findings of our recent analysis of UK NDNS RP 2008-2014 (28) , and therefore this area requires further exploration. While it is unlikely that the cereal fibre itself is positively associated with fasting glucose and HbA1c, potentially there is a characteristic of high cereal fibre, low whole grain diets that are affecting these associations.…”
Section: Discussionsupporting
confidence: 88%
“…Two other crosssectional studies supported these results [12,15]. In a recent crosssectional study of 2689 adults, whole grain intake was associated with lower CRP concentrations but as in our study, the association was attenuated to nonsignificant after adjusting for cereal fibre intake [27]. Another study in a sample of 5496 men and women demonstrated an inverse relationship between whole grain consumption and CRP levels, but after adjusting for BMI and insulin levels the association was no longer significant [28].…”
Section: Discussionsupporting
confidence: 81%
“…Considering fibre as an example, current UK intakes are woefully inadequate with the majority of every age group not meeting the revised target of 30 g/d (9) . Indeed, recent analyses have shown the importance of higher cereal fibre intake on markers of cardiovascular health such as lower waist-hip ratio (48) , in addition to being inversely associated with the prevalence of diverticular disease (49) and inflammation (50) . Thus, there is scope to utilise the overserving effect seen in our study to improve the population's intake of nutrients such as fibre; however, this requires input from manufacturers to reformulate products accordingly, reducing energy density of BC and simultaneously lowering salt and sugar.…”
Section: Discussionmentioning
confidence: 99%